GATEKEEPING MECHANISM IN THE SELECTION OF GUEST SPEAKERS FOR THE LIVE PROGRAM DAMAI INDONESIAKU ON TVONE - Rosdiana; RR. Roosita Cindrakasih (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
This study is motivated by the increasing challenges faced by mass media in maintaining public trust amid today’s information overload, particularly in live religious television programs. Religious talk shows carry a high credibility risk due to the limited ability to filter information in real time. This study aims to analyze the gatekeeping mechanism in selecting guest speakers for the Damai Indonesiaku program on tvOne, identify influencing factors, and examine the parties involved. The study applies the Hierarchy of Influences Theory by Pamela Shoemaker and Stephen D. Reese, encompassing five levels of influence: individual, media routines, organizational, extramedia, and ideological. A descriptive qualitative approach was employed, with data collected through observation, interviews, and documentation. Informants consisted of the Executive Producer, the Producer of Damai Indonesiaku, and a communication studies expert as triangulator. Findings reveal that gatekeeping occurs in sequential stages, beginning with weekly editorial meetings, speaker selection based on competence, credibility, public speaking ability, thematic relevance, and digital popularity, followed by schedule confirmation by the Talent Division, and final approval from the Deputy Editor-in-Chief. The process is influenced by KPI regulations, P3SPS standards, and the Press Council.